Lecturers' perspectives of pedagogical training initiates at a University of Technology in KwaZulu-Natal, South Africa - Gumede, P. R.; Sithole, M. P.; Gumede, D. (South African Journal of Higher Education, 2023)
Professional development of academics in higher education in South Africa has been offered in an uncoordinated and unsustainable manner. Ever since the new dispensation, concerted efforts have been implemented to address this problem. As part of the solution, universities through their academic development units, have introduced various pedagogical training workshops to equip academics with teaching skills. This study investigates perceptions of academics pertaining to this training. A multi-method cross-sectional research design was adopted to understand lecturers’ perspectives regarding professional development. A total of 45 participants were purposefully selected to participate in the study from the academics who attended the pedagogical training. A questionnaire (closed and open-ended) was used to collect data. Quantitative data were analysed using the Statistical Package for the Social Sciences (SPSS), while thematic analysis was applied to analyse qualitative data. Results of the study revealed that the training was well-received and academic staff members felt motivated and confident to implement various instructional strategies acquired from the training. Participants expressed a need and willingness to learn and develop new instructional techniques and acquired a positive outlook on teaching and learning following the professional development training. The study recommends redesigning the pedagogical training to include ongoing support activities and customisation in addition to the generic version.